Manajemen Strategi dan Implikasinya terhadap Efektivitas Rumah Sakit - Dedi Supriyadi; Fitri Utami Dewi; Purwadhi Purwadhi; Yani Restiani Widjadja (Lembaga Pengembangan Kinerja Dosen, 2026)
Hospital services possess unique characteristics that distinguish them from other service sectors due to their high complexity, direct interaction between healthcare providers and patients, simultaneous service delivery, and limited service capacity. This study aims to analyze the fundamental characteristics of hospital services through a Systematic Literature Review (SLR) to understand how the dimensions of intangibility, heterogeneity, inseparability, and perishability influence the quality of healthcare services. The review followed the PRISMA 2020 guidelines and utilized four major academic databases Scopus, PubMed, Google Scholar, and SINTA. From 1,214 identified publications, 60 articles met the eligibility criteria and were analyzed thematically. The results indicate that the intangible nature of services makes perceived quality highly dependent on communication and hospital reputation; heterogeneity is shaped by variations in staff competence and procedural implementation; inseparability emphasizes the critical role of patient–provider interactions; while perishability highlights the importance of effective demand and capacity management. This study concludes that a comprehensive understanding of these four service characteristics is essential for improving hospital service quality and strengthening patient experience, particularly through enhanced human resource capacity, standardized service processes, and the adoption of digital health technologies.